Effects of Caulerpa lentillifera added into culture media on the growth and nutritional values of Phronima pacifica, a natural fish-feed crustacean - Vivi Endar Herawati; Pinandoyo Pinandoyo; Restiana Wisnu Ariati; Nurmanita Rismaningsih; Seto Windarto; Slamet Budi Prayitno; Y.S. Darmanto; Ocky Karna Radjasa (Society for Indonesian Biodiversity, 2021)
Abstract. Herawati VE, Pinandoyo, Ariyati RW, Rismaningsih N, Windarto S, Prayitno SB, Darmanto YS, Radjasa OK. 2021. Effects of Caulerpa lentillifera added into culture media on the growth and nutritional values of Phronima pacifica, a natural fish-feed crustacean Biodiversitas 22: 424-431. Phronima pacifica is a microcrustacean commonly used as natural feed in fish farming as it has high nutrient contents and is suitable based on larval fish mouth gap size and mass cultivation capacity. However, P. pacifica is not produced optimally and its supply is inadequate, so that P. pacifica culturing techniques need to be improved. The culture of P. pacifica is mostly done using sea grape seaweed (Caulerpa lentillifera). The aim of this study was to investigate the optimal stocking density of C. lentillifera added into media culture on the growth and nutritional values of P. pacifica. We applied a complete random design experiment with four treatments of stocking density of C. lentillifera (i.e., 0 g/m2 (Control), 20 g/m2, 40 g/m2, and 60 g/m2) with 3 replicates for each treatment. The following parameters were analyzed, namely specific growth rate (SGR) of C. lentillifera, and the growth, biomass, growth rate, proximate analysis, and amino and fatty acid concentrations of P. pacifica. This study found that the addition of C. lentillifera into culture media significantly enhanced the growth of P. pacifica. The highest effect on the growth was observed in the treatment of 60 g/m2 with C. lentillifera SGR value of 4.76 ± 0.12%/day, and P. pacifica growth rate, population density and biomass of 4.41 ± 0.12 ind/day, 53.81 ± 8.79 ind/L, and 1.14 ± 0.14 g, respectively. Similarly, the highest protein and fat contained in P. pacifica was obtained in the treatment of 60 g/m2 with 60.23% protein and 10.24% fat. Furthermore, the highest fatty acid profile was C20: 5n-3 of 13.23% ± 0.08% and amino acid profile of 45.23% ± 0.01%. The application of the optimal stocking density of C. lentillifera in culture media could increase the growth and nutritional quality of P. pacifica which in turn could enhance aquaculture productivity.